PENGARUH SOSIAL MEDIA DAN ONLINE REVIEWS TERHADAP KEPERCAYAAN PELANGGAN DI KLINIK SAMARA BEAUTY CARE KECAMATAN PINANG - Delia Putri Isnaini; Purnawanti Purnawanti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. The purpose of this study is to examine the effect of social media and online reviews on customer trust at Samara Beauty Care Clinic, both partially and simultaneously. This study employs a quantitative method with an associative approach. Data were collected through questionnaires distributed to customers of Samara Beauty Care Clinic and analyzed using SPSS. The results of simple linear regression analysis indicate that social media has a positive effect on customer trust with the regression equation , while online reviews also have a positive effect with the regression equation . The t-test results show that social media has a significance value of 0.003 and online reviews have a significance value of 0.000, indicating that both independent variables have a significant partial effect on customer trust. Furthermore, the multiple linear regression analysis produces the regression equation . The simultaneous test (F-test) shows a significance value of 0.000, which is less than 0.05, indicating that social media and online reviews simultaneously have a significant effect on customer trust. The coefficient of determination test shows an R Square value of 84.1%, meaning that social media and online reviews explain 84.1% of the variation in customer trust, while the remaining 15.9% is influenced by other factors outside this study. The results of this study are expected to serve as a reference for management in developing effective digital marketing strategies to enhance customer trust. Keywords: social media, online reviews, customer trust, Samara Beauty Care